2019
DOI: 10.1159/000498838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Renal Function, Inflammation and Glycemic Control in Patients with Diabetic Nephropathy: a Systematic Review and Meta-Analysis

Abstract: Background/Aims: Vitamin D (VD) is widely recognized as renal protective. However, whether VD supplementation provides benefit to patients with diabetic nephropathy (DN) remains controversial. Here, we performed a meta-analysis to systematically evaluate the impact of VD supplementation on indexes of renal function, inflammation and glycemic control in DN patients, and to explore the potential renal protective mechanism of VD. Methods: We searched Pubmed, Embase, Cochrane Library, and three major Chinese biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Statistical analyses were carried out according to a previous published plan [12]. Results from 13 included RCTs were pooled and analyzed via Revman Review Manager version 5.3.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were carried out according to a previous published plan [12]. Results from 13 included RCTs were pooled and analyzed via Revman Review Manager version 5.3.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that VD supplements including calcitriol and alfacalcidol and 1,25(OH) 2 D 3 are beneficial for 24-hour urine protein and inflammation index and lessen high-sensitivity C-reactive protein (hs-CRP) but have no effects on hemoglobin A1c (HbA1c), serum creatinine (SCr), eGFR, and glycemic control index in DN patients. Besides, analysis based on different types of VD supplementations showed significant decreases of UAER and TNF-α in patients assigned to receive calcitriol [53]. Paricalcitol, a third-generation VD analog, is wildly used to prevent and treat DN leading to fewer episodes of hyperphosphatemia and hypercalcemia compared with calcitriol [54].…”
Section: The Role Of Vd/vdr Of the Clinical Treatment In Diabetic Nepmentioning
confidence: 99%
“…[ 17 ] Although our study is a short follow-up, in consistent with our's, a recent metanalysis showed that eGFR was not affected by vitamin D supplementation in DN patients. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%